Reception Analysis of the ‘Achieve Your Dreams with Us’ Campaign Among Second-Semester Students of Universitas 17 Agustus 1945 Surabaya - Djatmiko, Benedictus Raflin Algra Triyoga; Palupi, Merry Fridha Tri; Sadono, Teguh Priyo (Interaction Communication Studies Journal, 2025)
Intense competition among private higher education institutions (PHEIs) requires them to implement effective promotional campaigns to attract prospective students. This study examines the reception of second-semester students at Universitas 17 Agustus 1945 (UNTAG) Surabaya regarding the aspirational promise in the "Achieve Your Dreams with Us" promotional campaign. Employing a qualitative approach with reception analysis and Stuart Hall's encoding-decoding framework, data were collected through a Focus Group Discussion (FGD). The findings indicate that the most dominant reception position is the negotiated position. Students critically separated the slogan, which they perceived as "marketing language," and focused more on tangible evidence such as accreditation and tuition fees. They also reconstructed the meaning of "dreams" to align with their pragmatic goals (career, hobbies, self-development), while asserting that ultimate success depends on individual agency, with the university serving as a facilitator. A dominant position was found to emerge post-hoc following validation through positive real-world experiences on campus, whereas an oppositional position was absent. This study concludes that the reception of marketing messages by a young audience is not a passive process, but rather a complex act of pragmatic validation. In this process, the credibility of each message element (verbal, visual, symbolic) is actively negotiated based on the audience's frames of reference and experiences, in which concrete proof is valued over aspirational promises.